G382(P) Mind the gap! elevated anions secondary to paracetamol and sepsis. (27th April 2015) - Hulley, S; Perring, J; Manning, N; Olpin, S; Yap, S
Abstract : Aim: Metabolic acidosis is a common finding in children presenting with sepsis. Hypovolaemia and hypoxia are the common causes for this derangement but sometimes there are other culprits. We aim to highlight the significance of correlating the anion gap with the biochemical picture and, when there are discrepancies, look for alterative diagnoses. An unusual case of transient pyroglutamic aciduria, presenting during an episode of severe sepsis and paracetamol use, will be used to outline the importance of examining the anion gap. Methods: We illustrate the case of a 15 month old girl who presented with an 11 day history of diarrhoea and vomiting. She presented to the emergency department in a state of decreased consciousness. She was found to be hypotensive, hypoglycaemic and have a profound metabolic acidosis. She required mechanical ventilation and fluid resuscitation. Despite these interventions, she continued to have a profound metabolic acidosis with a very high anion gap (30.5). The levels of lactate and ketones were insufficient to explain the clinical picture. Results: Metabolic investigations for the child were instigated. Whilst a majority of these were normal, examination of the patient's organic acid profile revealed large peaks of pyroglutamic acid (5-oxoproline) and paracetamol. Termination of paracetamol use, administration of N-acetylcysteine to replenish the glutathione stores and haemofiltration caused resolution of the patient's acidaemia. Subsequent testing of the infants urine revealed no further evidence of pyroglutamate. Conclusions: Pyroglutamic aciduria (5-oxoprolinuria) is usually reported in children in the context of inherited errors of metabolism. The transient form that we describe here, whilst reported in the adult population, has rarely been described in children. Various pharmaceutical interventions, most commonly paracetamol, in combination with severe sepsis have been linked with this transient phenomenon. When the lactate and ketone levels don't correlate with the anion gap, it is important to pursue further diagnostic testing as illustrated by this case. In addition, scrutiny of the child's medication may give a clue to the diagnosis.